2022
DOI: 10.3389/fpsyg.2022.1026712
|View full text |Cite
|
Sign up to set email alerts
|

The scar that takes time to heal: A systematic review of COVID-19-related stigma targets, antecedents, and outcomes

Abstract: COVID-19, as a crucial public health crisis, has affected our lives in nearly every aspect. Besides its major health threats, COVID-19 brings severe secondary impacts, one of which is the rise of social stigma. Although numerous studies have examined the antecedents and outcomes of COVID-19-related stigma, we still lack a systematic understanding of who is being stigmatized during the COVID-19 pandemic, what exacerbates COVID-19-related stigma, and what impacts COVID-19-related stigma has on victims. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 120 publications
1
3
0
Order By: Relevance
“…Findings from this study confirmed the previous systematic review 45 but also went beyond that to provide a comprehensive picture of challenges experienced by participants during COVID-19. Participants expressed how social media had shaped negative mental pictures and social attitudes against them and how the COVID-19 news outbreak, misconceptions, rumors, and misinformation impede response efforts by fostering stigma and discrimination.…”
Section: Discussionsupporting
confidence: 86%
“…Findings from this study confirmed the previous systematic review 45 but also went beyond that to provide a comprehensive picture of challenges experienced by participants during COVID-19. Participants expressed how social media had shaped negative mental pictures and social attitudes against them and how the COVID-19 news outbreak, misconceptions, rumors, and misinformation impede response efforts by fostering stigma and discrimination.…”
Section: Discussionsupporting
confidence: 86%
“…Stigma and misunderstanding about Long COVID are prevalent, as evidenced by a qualitative study showing many participants encountering discrimination in healthcare settings 22. This lack of understanding and the resultant stigma or dismissive attitudes can be particularly distressing for those suffering from Long COVID 33. Finally, the unpredictable nature of Long COVID, including uncertainty about recovery, potential long-term impacts and possible effective treatments, can lead to significant anxiety and stress 34…”
Section: Discussionmentioning
confidence: 99%
“…22 This lack of understanding and the resultant stigma or dismissive attitudes can be particularly distressing for those suffering from Long COVID. 33 Finally, the unpredictable nature of Long COVID, including uncertainty about recovery, potential long-term impacts and possible effective treatments, can lead to significant anxiety and stress. 34 The findings of the current study have great public health and clinical implications.…”
Section: Open Accessmentioning
confidence: 99%
“…The authors also found that characteristics of the stigmatized, stigmatizer, and the context contribute to COVID-19 stigma, which negatively influence victims’ health and nonhealth outcomes. In some settings, specific survey measures have been developed to measure COVID-19 stigma and examine associations with attitudes and behavior (Zhou et al, 2022). Much of this measure development has been conducted in Asia, where health care workers and other persons presumed to be exposed to COVID faced significant stigma and discrimination (Huang et al, 2023; Nair et al, 2022).…”
mentioning
confidence: 99%